Rosai-Dorfman Disease Involving Multiple Organs: An Unusual Case with Poor Prognosis - Fandresena Arilala Sendrasoa; Irina Mamisoa Ranaivo; Onivola Raharolahy; Malalaniaina Andrianarison; Naina Harinjara Razanakoto; Lala Soavina Ramarozatovo; Fahafahantsoa Rapelanoro Rabenja (Case Reports in Medicine)
Rosai-Dorfman disease is a rare, benign histiocytic proliferative disorder that usually affects the lymph nodes. Although extranodal involvement has been reported in diverse sites, manifestation in the cardiovascular system is extremely rare. Specifically, cardiac involvement in Rosai-Dorfman disease is an extraordinarily infrequent event. We describe a case of a 36-year-old female who presented Rosai-Dorfman disease of multiple organs including the heart, with poor prognosis.